Why subaltern language? Yes, we speak Portuguese! For a critique of the coloniality of language in international student mobility - Borges, Rovênia (2018)
The ability to communicate in English is often associated with the condition of social class, gender and other factors of cultural identity. In this early 21st century, it has become one of the main constraints to participate in study and research programs in universities with top academic rankings. However, in many countries with too many educational inequalities, namely in Portugal and Brazil, the hegemony of the English language is a worrying factor for the internationalisation policies aimed at the high qualification of researchers in several scientific areas, especially those that lead to innovation and bring added value to the knowledge economy. From a comparative perspective, and taking into account some assumptions of postcolonial critical theories, this article presents a critical reflection on how English language teaching policies in the countries mentioned have acted to reinforce inequalities in terms of international student mobility.